Self-Implemented HIV Testing: Perspectives on Improving Dissemination Among Urban African American Youths - Catania, Joseph A. (Am J Public Health, 2015)
We examined the potential for increasing the reach of HIV testing to African American youths through the dissemination of oral-HIV testing. From 2012 through 2013 we examined the perceptions of alternatives to pharmacy dissemination of SITs in African American youths (5 focus groups) and service providers (4 focus groups), and conducted an ethnographic study of pharmacies (n = 10). Participants perceived significant advantages to delivering SITs through community health and services for adolescents (e.g., increased confidentiality, reduced stigma) over pharmacy dissemination. Given proper attention to fit, SIT dissemination could be facilitated through distribution by health and social service sites, and by improving elements of pharmacy dissemination.